Prior Sexual Victimization and Disclosure of Campus Sexual Violence Among College Students. Issue 1 (4th April 2019) - Stepleton, Kate; McMahon, Sarah; Potter, Cathryn C.; MacKenzie, Michael J.
Abstract : Using survey data from a large, public university, the authors examined the relationships of precollege sexual violence experience to revictimization and disclosure. Among victims of campus sexual violence, those with prior sexual victimization were no more or less likely to disclose to campus resources and were less likely to disclose to peers. Results suggest that institutions need to be prepared to support students with a range of victimization experiences. There is also a need for earlier and expanded sexual violence education and awareness efforts.